Novel distribution pattern between coexisting sexual and obligate asexual variants of the true estuarine macroalga Ulva prolifera1. Issue 11 (27th April 2016) - Hiraoka, Masanori; Higa, Motoki
Abstract: Where sexual and asexual forms coexist within a species, the asexuals are often found to be prevalent in marginal habitats. This asexual distribution pattern has received evolutionary attention linked to the paradox of sex. In many marine species, there is a distributional trend of asexual modes being more common in lower salinity waters regarded as the ecogeographic marginal, being explained by negative effects of low salinities on sexual reproductive success. However, the distribution pattern of estuarine species recently adapted to low salinity waters has remained unknown. The brackish macroalga Ulva prolifera being a major benthic component of estuarine ecosystems includes a sexual variant and obligate asexual variants by means of motile spores. We examined the sexual–asexual distribution pattern of this alga along a salinity gradient in river estuaries. Surprisingly, opposite to the distributional trend of marine organisms, the results clearly showed the persistent predominance of sexuals in the lower salinity reaches than the asexuals. In addition, a frequent alternating of dioecious gametophytes and sporophytes in the sexual population was observed, suggesting the sexual reproductive process would be robustly performed in the low salinity waters. Considering U. prolifera had evolved from the ancestral marine species to become a true estuarine species of which the core habitat is the low salinity reaches, in a broad sense its sexual–asexual distribution pattern would be involved in asexual marginal occupations of the species range previously reported in other organisms. Based on the frozen niche variation model, we can give a concise explanation for the evolutionary process of this pattern; multiple asexuals with frozen genotypic variation had arisen from sexual ancestors undergoing low salinity adaptation and share the estuarine habitat with the sexuals at present. Abstract : We reveal novel sexual–asexual distribution pattern in the true estuarine algal species Ulva prolifera which is a major benthic component of estuarine ecosystems and sympatrically includes sexual and obligate asexual variants.